Macbeth - Manson, Conrad (London : Usborne, 2005)
"Crystal, Lily and Poppy are three fairies in a flap. With stolen wands, flying lessons and Fairy Balls, there's never dull moment. Come to Fairyland and join in the magical fun" (publisher)
Keywords: Children's fiction